Simultaneous determination of levofloxacin and ciprofloxacin in human urine by ionic‐liquid‐based, dual‐template molecularly imprinted coated graphene oxide monolithic solid‐phase extraction. Issue 3 (27th December 2018) - Ma, Wanwan; Row, Kyung Ho
Abstract: A novel method was developed to simultaneously determine the ciprofloxacin and levofloxacin levels in human urine using an ionic‐liquid‐based, dual‐molecularly imprinted polymer‐coated graphene oxide solid‐phase extraction monolithic column coupled with high‐performance liquid chromatography. The molecularly imprinted monolithic column was prepared using ciprofloxacin and levofloxacin as templates, 1‐vinyl‐3‐ethylimidazolium bromide as the functional monomer, and graphene oxide as the core material. The resulting imprinted monoliths were characterized by scanning electron microscopy and fourier transform‐infrared spectroscopy. The efficiency and capacity of the ionic‐liquid‐based imprinted monolithic column were investigated by varying the synthesis conditions (ciprofloxacin/levofloxacin ratio and template/functional monomer/cross‐linker ratio). The solid‐phase extraction process was optimized by changing the washing and eluting conditions. The results suggested that the proposed ionic‐liquid‐based molecularly imprinted solid‐phase extraction monolithic‐high‐performance liquid chromatography method could separate ciprofloxacin and levofloxacin efficiently and simultaneously from human urine. The mean recoveries of ciprofloxacin and levofloxacin ranged from 89.2 to 93.8 and 86.7 to 94.6%, respectively. The intra‐ and interday relative standard deviation ranged from 0.9 to 3.2 and 0.8 to 2.9%, respectively. Under the optimized conditions, the recoveries of ciprofloxacin and levofloxacin were more than 93.8%.